(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2017)
The concept of cultural criticism in the knowledge field appeared in conjunction with the changes and transition related to post-modernism as it solicits from all knowledges and theories since it tackles culture in its entirety. This concepts works on revealing all, intellectual, speech prospective because it is a process of mental examination, deep cognitive digging to uncover the hidden patterns and interpret them; deconstructing meaning structures and establishments controlling its production and consumption to examine what is hidden in the folds of the speech to assume the cultural criticism partial tools and therefore, the researcher chose the topic of her current research (Cultural patterns in the contemporary pottery) and according to the above mentioned information the research was divided into four chapters. The first chapter tackled the problem of the research which dealt with taking the artistic text out of its isolation to the spot of speech concept and its openness and transition from shallowness of the shape that depends on the visible aesthetic images to uncovering this shape and reveal what’s hidden in the folds of the pottery speech and its responsivess to its cultural dominant moment? The second chapter (theoretical frame) contains two topics; the first topic discusses the concept of culture, cultural criticism references and mechanisms. while the two Topic is systemic approaches in the contemporary pottery. The theoretical frame was concluded with number of indicators resulted from this frame. The third chapter (research procedure) contains the research community represented by (40) contemporary American pottery works, research sample represented by (5) works, research tool, research method and samples analyzing. The fourth chapter contains research results and conclusions in addition to recommendations and suggestions.